Canva como recurso didáctico de enseñanza y aprendizaje de Anatomía Humana, en estudiantes de sexto semestre de la carrera de Pedagogía de la Química y Biología en el período, mayo 2021-octubre 2021 - Loja Veloz, Kerly Nicole (2022)
The main objective of this research is to propose Canva as a didactic resource for teaching and learning Human Anatomy due to teachers use little innovative support material, which does not allow the correct action of the student. The research design was non-experimental, descriptive, bibliographic, and field type. For data collection, the survey technique was used and the questionnaire as an instrument, with an intentional sample of 13 sixth-semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology career. The design of a digital book in Canva was proposed, in the Locomotion Systems and Nutrition and Excretion Systems units. Finally, it was concluded that these technological resources are support tools in teaching-learning processes in subjects such as Human Anatomy since they provide motivation and interest to teachers and students by offering varieties of information that guide learning and in turn improve the understanding of the contents.